2005
DOI: 10.1021/om050902e
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and Cationic Heteroscorpionate Aluminum Complexes:  Synthesis, Structure, and Ring-Opening Polymerization of ε-Caprolactone

Abstract: Treatment of 2,4-di-tert-butyl-6-(bis(3,5-dimethylpyrazol-1-yl)methyl)phenol (bpzmp-H) as tridentate ligand with aluminum trialkyls affords the corresponding heteroscorpionate aluminum complexes (bpzmp)-AlR 2 (R ) Me (1); R ) Et (2); R ) iBu (3)) in high yield. In the solid state, complexes 1-3 were isolated as racemic mixtures in which each stereoisomer adopts a tetrahedral structure with the bpzmp ligand κ 2 -coordinated to the metal via the phenoxy group and the imino nitrogen of one of pyrazolyl rings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…This type of fast exchange has already been extensively observed for other poly(pyrazol-1-yl)alkane complexes [30,31]. Scheme 1.…”
Section: Resultssupporting
confidence: 60%
“…This type of fast exchange has already been extensively observed for other poly(pyrazol-1-yl)alkane complexes [30,31]. Scheme 1.…”
Section: Resultssupporting
confidence: 60%
“…The NMR tube was vigorously shaken and a 1 H NMR spectrum was immediately recorded, showing the conversion of 3 + into the Al-hexyl cation 5 + along with the formation of poly(isobutene). After NMR analysis, the orange solution of [5] Tables 1 and 3. The cell parameters were determined from reflections taken from one set of ten frames (1.08 steps in f angle), each at 20 s exposure.…”
Section: Data For Chd 2 CLmentioning
confidence: 99%
“…[2] In this regard, some of these cations have already been used as alkene oxide, [3] (d,l)-lactide, [4] e-caprolactone, [5] and olefin [6] polymerization catalysts. Among this class of compounds, four-coordinate Alalkyl cations of the type [{LX}Al(R)(L)] + (LX À = bidentate monoanionic ligand, L = labile ligand) are the most studied as they combine a low-coordination with a cationic metal center, resulting in highly Lewis acidic species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[98][99][100][101][102][103][104][105][106][107] Nomura [98] studied the aluminum complexes containing phenoxyimine ligand for initiating polymerization of ɛ-caprolactone and found that the aluminum complexes 71 exhibited living polymerization characteristics when low monomer conversion, increasing conversion resulted in widening the PDI of PCL. Redshaw [99] also investigated the aluminum complexes 72 and 73 for ROP of ɛ-caprolactone, these catalyst system showed produced polymers with 44640 g/mol molecular weight, but, 46% monomer conversion.…”
Section: No Ligandmentioning
confidence: 99%